The commentary of literature and the problems of a poetic consciousness: Lev Tolstoy’s interpretation of the fragment of Ch. Dicken’s The Posthumous Papers of the Pickwick Club - Фортунатов, Николай (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The article is devoted to commenting on one of Tolstoy’s diary notes (1902), where he used fragments of Ch. Dicken’s The Posthumous Papers of the Pickwick Club.